1967
DOI: 10.1128/jb.94.4.972-983.1967
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Basis of Obligate Autotrophy in Blue-Green Algae and Thiobacilli

Abstract: Differential rates of incorporation of sugars, organic acids, and amino acids during autotrophic growth of several blue-green algae and thiobacilli have been determined. In obligate autotrophs (both blue-green algae and thiobacilli), exogenously furnished organic compounds make a very small contribution to cellular carbon; acetate, the most readily incorporated compound of those studied, contributes about 10% of newly synthesized cellular carbon. In Thiobacillus intermedius, a facultative chemoautotroph, aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
2

Year Published

1969
1969
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(102 citation statements)
references
References 43 publications
6
94
2
Order By: Relevance
“…Consistently with its putative signaling role, determinations of 2-oxoglutarate levels in different cyanobacteria incubated under different conditions of nitrogen supply have indicated accumulation of 2-oxoglutarate under N-limiting conditions [22][23][24][25]. Because cyanobacteria lack 2-oxoglutarate dehydrogenase [26], the main metabolic role of 2-oxoglutarate in these organisms is incorporation of nitrogen through the glutamine synthetase-glutamate synthase cycle [27], which positions 2-oxoglutarate at the link of C and N metabolisms.…”
Section: Nitrogen Control In Cyanobacteriamentioning
confidence: 97%
“…Consistently with its putative signaling role, determinations of 2-oxoglutarate levels in different cyanobacteria incubated under different conditions of nitrogen supply have indicated accumulation of 2-oxoglutarate under N-limiting conditions [22][23][24][25]. Because cyanobacteria lack 2-oxoglutarate dehydrogenase [26], the main metabolic role of 2-oxoglutarate in these organisms is incorporation of nitrogen through the glutamine synthetase-glutamate synthase cycle [27], which positions 2-oxoglutarate at the link of C and N metabolisms.…”
Section: Nitrogen Control In Cyanobacteriamentioning
confidence: 97%
“…It has been reported that the NAD-ICDH gene of Streptococcus mutans is encoded in an operon with citrate synthase and aconitase genes and is related to glutamate synthesis [14]. Although A. thiooxidans ICDH also can contribute to glutamate biosynthesis [8], the structure of the icd operon containing the putative succinyl-CoA synthetase gene is di¡erent from that of the icd operon of S. mutans. The complete analysis of the operon may reveal the physiological role of the 2-oxoglutarate-de¢cient TCA cycle containing NAD-ICDH of A. thiooxidans.…”
Section: Cloning Nucleotide Sequence and Expression Of The Icd Genementioning
confidence: 99%
“…Some chemolithotrophs, that possess a 2-oxoglutarate dehydrogenase-de¢cient TCA cycle, contain NAD þ -dependent ICDH (NAD-ICDH) activity [7,8], though most bacteria contain NADP þ -dependent ICDH (NADP-ICDH) activity. It has been reported that the incomplete TCA cycle functions for CO 2 ¢xation [9] as well as glutamate synthesis [8]. Thus, the bacterial NAD-ICDH is expected to be metabolically and structurally (especially the coenzyme recognition) unique, but little is known about the properties of the enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The poly-P-hydroxybutyrate fraction had almost 5 yo of the total 14C label recovered. This polymer has been shown to be an important constituent in the Nitrobacter cell functioning as an energy reserve (Tobback & Laudelout, 1965).…”
Section: Growth On An Alternative Inorganic Compound or On Organic Comentioning
confidence: 99%
“…The debate on what constitutes the distinctive characteristics of the autotrophic mode of life continues and this now embraces not only nitrifying bacteria but also the sulphur oxidizing thiobacilli and the photosynthetic autotrophically grown, blue-green algae. Ever since the report of Smith, London & Stanier (1967) that several obligate autotrophs, blue-green algae and chemosynthetic bacteria, lacked a-ketoglutarate dehydrogenase and NADH oxidase many workers have not confirmed this evidence. Pearce & Carr (1967) noted the absence of the dehydrogenase from the blue-green alga Anabaena vulgaris, suggesting an incomplete tricarboxylic acid cycle.…”
Section: Addendummentioning
confidence: 99%